2017
DOI: 10.17059/2017-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Positioning of Small and Medium Enterprises in Bangladesh, Thailand and the Philippines

Abstract: Small and Medium Enterprises (SMEs) play a significant role in the nation's economic development process. SMEs provide job opportunities, create wealth, promote modernization and contribute to technological changes. The Asia-Pacific Region is foreseen to be the next economic boom. A comparison of SMEs in Bangladesh, Thailand and the Philippines on their SMEs Landscape, Banking sector, Non-Banking sector and Capital Markets would give a picture of which strengths, weaknesses, opportunities and threats these cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Following this idea, companies become dynamic agents of the economy, offering new job opportunities, creating wealth, within modernization and adoption of technological changes [19]. In Latin America, the labor business context is more complex, due to the region's peculiarities in the economic, commercial, technological, and poverty fields [20]. Following this idea, some reports highlight the consequences that self-employed workers have suffered due to the pandemic, including the loss of their jobs and even their homes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Following this idea, companies become dynamic agents of the economy, offering new job opportunities, creating wealth, within modernization and adoption of technological changes [19]. In Latin America, the labor business context is more complex, due to the region's peculiarities in the economic, commercial, technological, and poverty fields [20]. Following this idea, some reports highlight the consequences that self-employed workers have suffered due to the pandemic, including the loss of their jobs and even their homes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The study shows the employment of older people should take into account their higher potential compared to the overall employment. Employment of older people is inherently limited, since their ability to choose work activities is significantly narrowed by a biased attitude towards an elderly person [19].…”
Section: Resultsmentioning
confidence: 99%
“…The Office of Small and Medium Enterprises Promotion (OSMEP) (2017) reported that of the 3,004,679 SMEs recorded in Thailand, small enterprises (SEs) amounted to 1,183,376 and accounted for nearly 2.47 trillion baht (about US$78.8bn) in revenue, or 29.7% of overall GDP in 2016. Most SMEs in the service sector belong to the tourism and hospitality sector (Tambunan, 2008) and make the largest contribution to total SME employment (Ali et al , 2017).…”
Section: Methodsmentioning
confidence: 99%